The valuable essence of punishment in the canon law of the Roman Catholic tradition - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2019)
The nature of punishment in canon law of the Roman Catholic tradition through the prism of its reflection of a person’s attitude to Christian values is explored. The valuable essence of punishment is revealed, depending on what values it protects and for violating of what it is appointed. The concept of free will and guilt of a man in Christian doctrine is studied, the basis for punishability for crimes is grounded. The author reveals important features in the provisions of the Code of Canon Law of the Roman Catholic (Latin) Church concerning the origin of the legitimacy of power, the content and types of punishment, the origin of the law of conviction, punishment and its execution. It is stated that in the doctrine of the Roman Catholic Church the main foundation of cognition of the essence of punishability and the law of punishment is the Holy Scripture and the Christian tradition. It is proved that the ranking of the types of punishment for violations of publicly protected goods reflects the hierarchy of values, adopted by society, based on the degree of their priority and importance. It is concluded that one of the central places in the modern doctrine of punishment, including the penal law, should take axiological and anthropological methodologies.